2016
DOI: 10.18276/cej.2016.4-09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Shoulder Joint Strength Disproportion of Masters Swimmers

Abstract: The aim of this study was to find out whether Masters class swimming affects strength disproportion and if there is a correlation between the length of sport swimming training in Masters swimmer's past (SST) and strength parameter's deficits? Eighteen Masters category swimmers affiliated in Szczecin Masters Team (178.3 ±2.28 m; 77.9 ±2.86 kg) participated in the study. Isokinetic strength measurement was made on Biodex S4 dynamometer. Subjects performed shoulder flexion/extension moves: 3 repetitions -60 deg/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Likewise, in the left ankle, 10.51 (11.02) was observed in males and 7.99 (3.78) in females. In both cases, these values were even lower than the 10% seen in other knee studies [ 48 , 49 ], or even the 15% found in other joints [ 50 ]. These values are important because they provide reliability [ 51 ] to the collaboration of the subjects.…”
Section: Discussioncontrasting
confidence: 68%
“…Likewise, in the left ankle, 10.51 (11.02) was observed in males and 7.99 (3.78) in females. In both cases, these values were even lower than the 10% seen in other knee studies [ 48 , 49 ], or even the 15% found in other joints [ 50 ]. These values are important because they provide reliability [ 51 ] to the collaboration of the subjects.…”
Section: Discussioncontrasting
confidence: 68%
“…isokinetic analysis of arm movements in several planes (Beach et al, 1992;McMaster et al, 1992;Magnusson et al, 1995;Alonso-Cortés Fradejas et al, 2006;Van De Velde et al, 2011;Nakashima et al, 2012;Manske et al, 2015;). On the other hand, a significant gap in strength studies concerning the flexion and extension movements of the arm has been noted (Moffroid et al, 1969;Wattanaprakornkul et al, 2011;Girold et al, 2012), so a study of our own was initiated (Wiażewicz, 2016;Wiażewicz and Eider, 2016).…”
Section: Strength Measurement Methods Used In Competitive Swimmingmentioning
confidence: 99%
“…The aim of the study by Wiażewicz and Eider (2016) was to investigate whether Masters swimming affects strength disparity? Additionally, the correlation between the number of years of sports swimming training in a swimmer's past and the deficit in strength parameters was analysed.…”
Section: Strength Measurement Methods Used In Competitive Swimmingmentioning
confidence: 99%
“…Так, для організації занять із дітьми дошкільного віку доцільно використовувати басейни з ваннами таких розмірів -7/3 м, 10/6 м, 12,5/6 м, із глибиною до 1 -1,6 м. [6,7,15].…”
Section: результати дослідження та їх обговоренняunclassified